A Comparison of Two Arthroscopic Techniques for Interpositional Polytetrafluoroethylene Patch Repair for Massive Irreparable Rotator Cuff Tears: Speed and Biomechanics. Issue 2 (July 2018) - Sunwoo, Joo Y.; Lam, Patrick H.; Murrell, George A. C.
Background: Interpositional synthetic patch repairs are a novel method of treating massive irreparable rotator cuff tears. However, surgeons experience difficulty in the arthroscopic insertion of these patches. Questions/Purposes: We compared two methods of arthroscopic interpositional synthetic patch repair: the newly devised slide-and-grip technique, using pre-loaded sliding knots and no arthroscopic knots, and the weave technique, using less arthroscopic knot tying than the earlier mattress technique. Study questions were as follows: (1) Would the slide-and-grip technique take less time than the weave technique? (2) Would the biomechanical strength of the two methods be comparable? Methods: Fourteen paired ovine infraspinatus tendon ex vivo models of the degenerative human rotator cuff underwent timed repair with a synthetic polytetrafluoroethylene (PTFE) patch, using either the weave technique ( n  = 7) or the slide-and-grip technique ( n  = 7). Each was pulled to failure using a tensile testing machine, the Instron 8874. Results: The time to complete the slide-and-grip repairs was shorter (12 ± 0.9 min) than that of the weave repairs (23 ± 1 min). Ultimate load to failure was comparable for the slide-and-grip and weave techniques (211 ± 27 N vs. 295 ± 35 N, respectively), and the slide-and-grip was less stiff (14 ± 1 N/mm vs. 19 ± 1 N/mm). Conclusions: The slide-and-grip technique took less time than the weave technique for the interpositional patch repair of massive irreparable rotator cuff tears and when correctly performed had comparable biomechanical strength.